2008
DOI: 10.1021/pr800318j
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Complex Protein Mixture by Virtual Three-Dimensional Liquid Chromatography Based on Combined pH and Salt Steps

Abstract: The complexity and diversity of biological samples in proteomics require intensive fractionation ahead of mass spectrometry identification. This work developed a chromatographic method called virtual three-dimensional chromatography to fractionate complex protein mixtures. By alternate elution with different pHs and salt concentrations, we implemented pH and salt steps by turns on a single strong cation exchange column to fully exploit its chromatographic ability. Given standard proteins that were not resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…The output results were combined by BuildSummary software with a false positive rate (FPR) less than 1% as the filtration criterion. The FPR was calculated as double of the number of peptides from reversed database divided by the number of peptides from reversed and normal database [46]. The protein identification criteria were based on Delta CN (≥0.1) and cross-correlation scores (Xcorr, one charge≥1.9, two charges ≥2.2, three charges ≥3.75).…”
Section: Methodsmentioning
confidence: 99%
“…The output results were combined by BuildSummary software with a false positive rate (FPR) less than 1% as the filtration criterion. The FPR was calculated as double of the number of peptides from reversed database divided by the number of peptides from reversed and normal database [46]. The protein identification criteria were based on Delta CN (≥0.1) and cross-correlation scores (Xcorr, one charge≥1.9, two charges ≥2.2, three charges ≥3.75).…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples have poor rheological properties that may lead to high back pressures, column fouling, and drastically shortened analytical column life . In contrast to analytical chromatography that typically relies on a binary buffer system, batch chromatography samples are bound to the stationary phase of the column and eluted in one or many different fractions by a step-gradient of ionic strength or pH Guerrier, Lomas, & Boschetti, 2007;Guerrier et al, 2008;Kreusch et al, 2008;Ning et al, 2008;Tucholska et al, 2009). Separation of intact proteins using a novel library of peptides (Guerrier et al, 2006) as a stationary phase was observed to work well (Baussant et al, 2005;Sennels et al, 2007;Sihlbom et al, 2008).…”
Section: B Batch Preparative Chromatographymentioning
confidence: 99%
“…Partition chromatography has a high sample capacity and the resolving power of the column depends on its length, the number of plates, the relative amount of sample loaded, plus the selectivity of the different loading and eluting buffers used in the experiment (Ning et al, 2008;Tucholska et al, 2009). Many proteins were purified from blood fluids using sequential chromatography (Duckert, Koller, & Matter, 1953;Kanai, Raz, & Goodman, 1968;McConnell & Mason, 1970;Murthy & Hercz, 1973;Poffenbarger, 1975;Tollefsen, Majerus, & Blank, 1982).…”
Section: Partition Chromatography Of Proteins and Peptidesmentioning
confidence: 99%
“…Further extensions of multiple chromatographic approaches (3D-LC [36]) can increase LC-MS time to the point where stability of the system might become an issue;…”
Section: Challengesmentioning
confidence: 99%